2008
DOI: 10.1002/jsc.824
|View full text |Cite
|
Sign up to set email alerts
|

Planning with Blue Ocean strategy in the United Arab Emirates

Abstract: ᭹ Blue Ocean strategy emphasizes revisiting the value added of various activities in the value chain. Key activities should have added value whilst other activities should have reduced value. Some activities should be eliminated and new activities should be introduced. ᭹ Non-customers should be targeted through innovation and change in strategy rather than competing head-on with direct competitors. In the UAE, new businesses are starting in a high-growth economy and new strategies are being implemented by smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 10 publications
0
5
0
1
Order By: Relevance
“…Blue Ocean strategy emphasizes focusing on the value added activities in the value chain whilst eliminating the activities with reduced value (Butler, 2008). The ERRC The ERRC grid of Tuzak, eliminate, reduce, raise and create phases of their blue ocean strategy phases is demonstrated in Table 3.…”
Section: Fig 1 Tuzak's Move To Blue Ocean Againmentioning
confidence: 99%
“…Blue Ocean strategy emphasizes focusing on the value added activities in the value chain whilst eliminating the activities with reduced value (Butler, 2008). The ERRC The ERRC grid of Tuzak, eliminate, reduce, raise and create phases of their blue ocean strategy phases is demonstrated in Table 3.…”
Section: Fig 1 Tuzak's Move To Blue Ocean Againmentioning
confidence: 99%
“…Chang (2010) conducted a study investigating cell phone markets using BOS and found bandit (i.e., unbranded or unknown-brand "white box" cellphones) introduced new business model changing the rule of game having low-cost and high value-added features. Butler (2008) did a study in UAE on both small and medium enterprise and multi-national enterprise sectors where new strategies and economy are implemented investigating the BOS. They mentioned that in BOS, revisit of value added activities are emphasized, some activities are eliminated and new activities introduced, noncustomers are targeted through innovation and changing strategy than competing intense competition.…”
Section: Bos Implementation Cases and Impactmentioning
confidence: 99%
“…Because of inadequate technology and social infrastructures mentioning electricity and fuel crisis, the selected firms were not performing well. "Improvement in productivity is due not only to technology, but also to how it's integrated into the organization" (Gagnon & Dragon, n.d., p. 19). Integration of diversity is relevant in world demographic patterns and work practices (Simons & Rowland, 2011).…”
mentioning
confidence: 99%
“…[37] also provided an application of the Blue Ocean Strategy to develop new products, and she reached a strategic approach that can be applied to product development. [38] also introduced an experimental study on five managers in the United Arab Emirates for the Blue Ocean Strategy and how that enables small and large companies (based on their abilities) to open a new undisputed space in the market, and to focus on non-customers instead of the current customers as well as to focus on what the existing customers have in common. [39]'s study focused on logistics service providers (PL3) in South Korea and how they can be leading in this modern industry, using the framework of the Blue Ocean Strategy.…”
Section: The Relationship Between Blue Ocean Strategy and Competitivementioning
confidence: 99%